2015
DOI: 10.2135/cropsci2014.09.0655
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Pentaploid Buffelgrass Accessions

Abstract: Buffelgrass [Pennisetum ciliare (L.) Link (syn. Cenchrus ciliaris L.)], an important pasture and range grass in the arid semi‐tropics and tropics, has excellent drought‐tolerance but lacks winter hardiness. It is a polymorphic, apomictic species and its most common chromosome number is 2n = 4x = 36. Eighty‐six pentaploid (2n = 5x = 45) accessions from South Africa were deposited into the USDA National Germplasm System (NPGS) in 1976 and these were more winter‐hardy than all tetraploid accessions. Prior to 1976… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
5
7
0
2
Order By: Relevance
“…The highest internode length (24.08 cm) occurred in Nigerian accession NGB00537 (Table 2). To corroborate the present results, according to Hash et al (2003) and Burson et al (2015), gene actions and environmental influences have great effects on vegetative and yield performance of cereals. Furthermore, it has been demonstrated that particular genotypes perform best in particular environments because of favoured interactions (Mano and Takeda, 1995).…”
Section: Resultssupporting
confidence: 87%
“…The highest internode length (24.08 cm) occurred in Nigerian accession NGB00537 (Table 2). To corroborate the present results, according to Hash et al (2003) and Burson et al (2015), gene actions and environmental influences have great effects on vegetative and yield performance of cereals. Furthermore, it has been demonstrated that particular genotypes perform best in particular environments because of favoured interactions (Mano and Takeda, 1995).…”
Section: Resultssupporting
confidence: 87%
“…These grasses are widely established and continue to be sown following brush clearing, particularly in Texas and Mexico (Arriaga et al 2004, Lyons et al 2013. The geographic range of buffelgrass is limited because the grass lacks cold tolerance (Burson et al 2015), but its range may expand in the future with predicted changes in climate (Archer and Predick 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Actualmente, es la especie más utilizada en la rehabilitación y conservación de suelo en pastizales de zonas áridas y semiáridas (2) señalándose inclusive, que es la especie clave para el desarrollo de la ganadería del norte y centro de México (3,10,11) . El pasto buffel es quizá, una de las especies más estudiadas en los últimos años; los reportes incluyen diferentes tópicos, desde estudios genéticos (12,13) , fisiológicos (14,15) , ecológicos (9,16) , de establecimiento, adaptación distribución (3,17) , valor nutricional (18) y productividad (3,8) . Actualmente se cuenta con líneas experimentales e híbridos que se han desarrollado en México (18,19,20) y se han utilizado variedades registradas en el extranjero (3,21,22) , pero que no han sido registradas en el país, ante el Servicio Nacional de Inspección y Certificación de Semillas (SNICS), órgano oficial de la SAGARPA en México para el registro de nuevas variedades.…”
Section: Origenunclassified